BRONCHIAL ASTHMA: MODERN VIEWS OF RISK FACTORS (Modern education and development, 2025)
The most significant factor for the development of bronchial asthma is atopy. Atopy is a tendency to produce increased amounts of IgE in response to exposure to environmental allergens and is inherited maternally in an autosomal dominant pattern. In population studies, it has been shown that the majority of children and adults with proven bronchial asthma had atopy. Genetic factors in bronchial asthma have received special attention; clinical and genealogical analysis reveals a hereditary nature of asthma in one-third of patients. At least three groups of genes are known to be responsible for the control of allergic sensitization and total IgE levels (atopy genes), bronchial lability (bronchial hyperreactivity genes) and the development of inflammation in asthma [12,13,14].